Answer:
Solutions:
,
![x = (-3)/(4) - i √(39)](https://img.qammunity.org/2022/formulas/mathematics/high-school/aiocg6womdxoeow8tr597780dvrcoaj2xr.png)
Explanation:
Given the quadratic equation, 2x² + 3x + 6 = 0, where a =2, b = 3, and c = 6:
Use the quadratic equation and substitute the values for a, b, and c to solve for the solutions:
![x = \frac{-b +/- \sqrt{b^(2) - 4ac} }{2a}](https://img.qammunity.org/2022/formulas/mathematics/college/247aptq48wjc43bc9cin0ma4sxcgjyujww.png)
![x = \frac{-3 +/- \sqrt{3^(2) - 4(2)(6)} }{2(2)}](https://img.qammunity.org/2022/formulas/mathematics/high-school/7txwu3jyw2y196yzurja9zplxx8ec3fmiq.png)
![x = (-3 +/- √(9- 48) )/(4)](https://img.qammunity.org/2022/formulas/mathematics/high-school/s5xcw48oykrh2hpux3aiunxzlnr248juzw.png)
,
![x = (-3 - i √(39) )/(4)](https://img.qammunity.org/2022/formulas/mathematics/high-school/5iwt8alttgd3jlciazi64xb7ldrk2672l0.png)
Therefore, the solutions to the given quadratic equation are:
,
![x = -(3)/(4) - i √(39)](https://img.qammunity.org/2022/formulas/mathematics/high-school/wnn9vhi8wsm5zd6i79iiktt9cnfmqstal9.png)